Ionizing radiation reduces glutathione levels in the eye: A pilot study. Issue 2 (June 2022) - Sun, Lue; Inaba, Yohei; Sogo, Yu; Kunugita, Naoki; Chida, Koichi; Moritake, Takashi
Abstract: In 2011, the International Commission on Radiological Protection recommended reducing the threshold dose and occupational equivalent dose limit for the lens of the eye. However, this recommendation was based on limited epidemiological evidence and a few assumptions. Additional epidemiological and biological studies are thus required to understand radiation cataracts and optimize radiation protection practices. Glutathione is present in large amounts in the lens and inhibits the onset and progression of cataracts. A few studies have reported changes in glutathione levels in laboratory animal lenses after irradiation, but evidence about dose rate and time dependence remains lacking. In this study, we analyzed dose rate- and time-dependent changes in whole-eye reduced glutathione (GSH) and oxidized glutathione (GSSG) levels after γ-irradiation. We found that both decreases in eye GSH levels and delays in eye GSH recovery depended on dose rate. Our results support the concept that changes in GSH levels influenced on radiation cataractogenesis, consistent with previous biological research. This study will contribute to the mechanistic understanding of radiation cataractogenesis.